2023
DOI: 10.21203/rs.3.rs-2484330/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The 3Po states of exotic molecular ions with exponential-cosine-screened Coulomb potentials

Abstract: We investigate the bound states, Borromean states and resonant states for the 3Po (J = 1) states of \(pp\mu\), \(dd\mu\) and\(tt\mu\) molecular ions interacting with exponential-cosine-screened Coulomb potential. The bound 3Po state energies are calculated using the Rayleigh-Ritz variational method and the resonance parameters are calculated using the stabilization method. Highly correlated exponential wave functions are used. The bound 3Po state energies, the 3Po resonance parameters (energy and width), along… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…They enable the development of new mathematical and theoretical models and can lead to various technological applications. The Borromean states and resonant states of molecular ions under the effect of exponential cosine screened Coulomb potential, such as ppμ, ddμ, and ttμ, have been theoretically investigated [16]. In this study, critical values of the screening parameter for Borromean correlations are reported.…”
Section: Introductionmentioning
confidence: 99%
“…They enable the development of new mathematical and theoretical models and can lead to various technological applications. The Borromean states and resonant states of molecular ions under the effect of exponential cosine screened Coulomb potential, such as ppμ, ddμ, and ttμ, have been theoretically investigated [16]. In this study, critical values of the screening parameter for Borromean correlations are reported.…”
Section: Introductionmentioning
confidence: 99%